Potentials and Limitations of Educational Videos on YouTube for Science Communication - Kohler, Sarah; Dietrich, Tabea Clara (Frontiers in Communication, 2021)
YouTube has become a complement learning platform which fosters learning on demand with educational videos. Educational videos are understood as a fruitful strategy to enhance the user’s knowledge and are applied in schools, as well as in science communication, e.g. to inform about climate change. This paper discusses two perspectives which become visible in the current research literature on educational videos on YouTube. First, studies assume that watching educational videos changes the attitude or behavior of the recipients. Second, studies question whether educational videos have a higher impact than other information materials such as texts. We frame both perspectives with regard to theories from media effect studies and learning concepts from education science and discuss their conclusions for educational videos on YouTube. We will first focus on students as a target group for educational videos, but in the further course, we will discuss the results for the public as targeted group of science communication as well. In the final section we will summarize which potentials and limitations educational videos have for educational purposes in science communication.